The Role of the Police Security Intelligence Unit in Disclosing Murder Cases (Case Study at the Rembang Police) - Rochmad, Miftakur; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
The crime of murder is a form of crime that has a serious impact on the stability of security and public order. In dealing with this crime, law enforcement efforts are needed that are not only reactive, but also preventive and strategic. One important element in the process of revealing murder cases is the role of the police Intelligence and Security Unit in helping to reveal murder crimes. This study aims to determine, examine, and analyze the role of the police security intelligence unit in revealing the case of murder at the Rembang Police, obstacles and solutions to the role of the police security intelligence unit in revealing the case of murder at the Rembang Police, and the concept of the role of the police security intelligence unit in revealing the case of murder in the future based on legal certainty. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data source used is primary data. While secondary data is obtained from literature study research consisting of primary legal materials, secondary legal materials, and testier legal materials. Based on the results of the study, it can be concluded that the role of the police security intelligence unit in uncovering the murder case at the Rembang Police is to play an important role in supporting the investigation and inquiry process, which plays a role in collecting initial information, analyzing and evaluating information, coordinating with the Criminal Investigation Unit (Satreskrim) and monitoring the security situation. Obstacles and solutions to the role of the police security intelligence unit in uncovering the murder case at the Rembang Police are limited personnel and operational facilities, the difficulty of digging up information from the public, invalid information and hoaxes on social media, the solution is to increase the capacity of personnel and intelligence facilities, strengthen partnerships with the community, manage digital information and intelligence literacy, optimize cross-functional coordination, and uphold neutrality and intelligence ethics. The concept of the role of the police security intelligence unit in uncovering murder cases in the future based on legal certainty, namely by strengthening the legal basis of police intelligence, using standardized technology, conducting cross-unit coordination that is orderly by law, and increasing professionalism and intelligence ethics.